ALLOMETRICALLY SCALED H:Q RATIOS: TIME TO SHARPEN OUR VISION CONCERNING STRENGTH RATIOS AS INJURY RISK FACTOR!. Issue 4 (1st February 2017) - Radin, Rafeeuddin; Sharir, Raihana; Robinson, Mark; George, Keith; Atkinson, Greg; Lolli, Lorenzo; Konopinski, Matt; Vanrenterghem, Jos
Abstract : Background: Our recent systematic review showed that prospective studies found contradicting results concerning hamstring-quadriceps (H:Q) strength ratios as a risk factor for ACL injuries. All studies that express hamstring relative to quadriceps strength assume a proportional relationship yet this is not likely. Objective: i) To investigate if the H:Q strength relationship is proportional in athlete populations and ii) To evaluate the differences in participant rankings between the traditional way of calculating H:Q ratios and allometrically scaled H:Q ratios. Design: Controlled laboratory study. Setting: The study was conducted both in a club and biomechanics laboratory setting. Participants: 71 male elite football athletes, 55 male recreational athletes and 48 female recreational athletes participated in the study. Assessment of Risk Factors: Concentric hamstring and quadriceps strength (Hcon and Qcon), and eccentric hamstring strength (Hecc) were tested in participants' dominant and non-dominant limbs using isokinetic dynamometry at an angular velocity of 60°/s. Main Outcome Measurements: i) Allometric exponents (AE) of the Hcon:Qcon and Hecc:Qcon relationships and ii) Chi-square relationships between population rankings based on the traditional H:Q ratios and the allometrically scaled H:Q ratios. Results: i) Linear regression analyses showed that the Hcon:Qcon and Hecc:Qcon relationships were systematically non-proportional (AE ranged between 0.61 and 0.84) and ii) correcting H:Q ratios based on an average allometric exponent (0.65 for Hcon:Qcon and 0.78 for Hecc:Qcon) successfully removed bias from quadriceps strength, and significantly altered population rankings. Conclusions: Quadriceps strength meaningfully affects H:Q ratios, causing bias in proportionally scaled H:Q ratios. Unless if quadriceps strength itself is a risk factor, allometrically scaled H:Q ratios are a superior measure of H:Q strength (im)balance for injury risk analyses in athlete populations.